2021
DOI: 10.1038/s41598-021-83375-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change as a driver of food insecurity in the 2007 Lesotho-South Africa drought

Abstract: Climate-induced food production shocks, like droughts, can cause food shortages and price spikes, leading to food insecurity. In 2007, a synchronous crop failure in Lesotho and South Africa—Lesotho’s sole trading partner—led to a period of severe food insecurity in Lesotho. Here, we use extreme event attribution to assess the role of climate change in exacerbating this drought, going on to evaluate sensitivity of synchronous crop failures to climate change and its implications for food security in Lesotho. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…This corroborates the findings of Kralovec ( 2020 ) and Muringai et al ( 2020 ), which found that declining water resources, higher temperature and rising CO2 emission have a negative effect on food security due to the impact on agricultural productivity. Also, Verschuur et al ( 2021 ) found out that climate change was a major driver of food insecurity in the drought that was experienced in Lesotho-South Africa in 2007. Hence, a 1% increase in GHG emission results in 1.391% decline in food security or rise in prevalence of malnourishment rate.…”
Section: Estimation and Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This corroborates the findings of Kralovec ( 2020 ) and Muringai et al ( 2020 ), which found that declining water resources, higher temperature and rising CO2 emission have a negative effect on food security due to the impact on agricultural productivity. Also, Verschuur et al ( 2021 ) found out that climate change was a major driver of food insecurity in the drought that was experienced in Lesotho-South Africa in 2007. Hence, a 1% increase in GHG emission results in 1.391% decline in food security or rise in prevalence of malnourishment rate.…”
Section: Estimation and Interpretation Of Resultsmentioning
confidence: 99%
“…Furthermore, a study by Verschuur et al ( 2021 ) used an extreme event attribution (EEA) approach and was combined with an explanatory framework that examined climate change impact on worsening food production shocks in Lesotho. More precisely, they evaluated how crops are sensitive to climate change and gave some insights into its implications for food security.…”
Section: Brief Review Of Empirical Literaturementioning
confidence: 99%
“…We also identified multiple low amplitude of precipitation in 1992, 2007, and 2018 in the complete study area. The low precipitation in 2007 was the event that responsible for crop failures and led to food insecurity across the study regions and including the neighboring country Lesotho 73 . According to Masupha and Moeletsi 74 , in the near future (2020/21–2036/37) and far future (2055/56–2089/90), the reduction of soil moisture will be more pronounced which will have negative impact on rainfed maize performance in the Luvuvhu river catchment area, north-eastern part of South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Values of PR > 1 imply that climate change contributed to a certain event occurrence; for instance, PR = 2 implies that climate change made a certain event class (typically defined as all events exceeding a critical threshold) two times more likely. So far, attribution studies have mainly treated events as univariate, though studies on compound event attribution are emerging 44,[46][47][48] .…”
Section: Compound Event Attributionmentioning
confidence: 99%